2014
DOI: 10.1007/s00261-014-0154-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive assessment of liver fibrosis in patients with alcoholic liver disease using acoustic radiation force impulse elastography

Abstract: ARFI elastography is an acceptable method for predicting the severity of fibrosis in patients with ALD. ARFI elastography is influenced by elevated aminotransferase levels in ALD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 27 publications
0
25
0
1
Order By: Relevance
“…Point SWE has proven diagnostic assessment in liver fibrosis in patients with chronic viral hepatitis B and C, alcoholic and non-alcoholic steatohepatitis [18][19][20][21]. Also, the ARFI technique is used in the assessment of liver fibrosis, in the pathology of the thyroid, breast, prostate, and lymph nodes [9,[22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Point SWE has proven diagnostic assessment in liver fibrosis in patients with chronic viral hepatitis B and C, alcoholic and non-alcoholic steatohepatitis [18][19][20][21]. Also, the ARFI technique is used in the assessment of liver fibrosis, in the pathology of the thyroid, breast, prostate, and lymph nodes [9,[22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…These techniques have been employed to assess the mechanical elasticity of various organs of different shapes and sizes. Previous studies showed promising results in evaluating liver fibrosis (Palmeri et al, 2011, Bavu et al, 2011, Nierhoff et al, 2013, Sporea et al, 2013 and Zhang et al, 2014), breast lesions (Meng et al, 2011), vascular plaques (Doherty et al, 2012), prostate cancers (Zhai et al, 2012 and Correas et al, 2013), and muscle anisotropy(Gennisson et al, 2010). Other organs where ARFI and SWEI have been explored include the bladder (Nenadic et al, 2013), cervix (Feltovich et al, 2012), and cornea (Tanter et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [90] showed a strong correlation (r = 0.685, p < 0.001) between histological fibrosis and liver stiffness in patients with ALD, as measured by ARFI elastography. Using the Scheuer scoring system for histologic grading of fibrosis, they found areas under the receiver operating characteristic curve of 0.846 and 0.893 for the differentiation of significant fibrosis ( ‡S2) and cirrhosis (S4), respectively [90].…”
Section: Alcoholic Liver Disease (Ald)mentioning
confidence: 97%
“…Using the Scheuer scoring system for histologic grading of fibrosis, they found areas under the receiver operating characteristic curve of 0.846 and 0.893 for the differentiation of significant fibrosis ( ‡S2) and cirrhosis (S4), respectively [90].…”
Section: Alcoholic Liver Disease (Ald)mentioning
confidence: 99%